Histologic and radiological observations of a human immature premolar with pulp necrosis treated with regenerative endodontic procedure - A case report of a four-year follow-up - Kanwardeep Kaur; Eby Varghese; Uma Eswara; Joanne Goh Pei En (Elsevier, 2023)
Background: Reports are found on long-term radiographic follow-up of teeth treated with regenerative endodontic techniques, but scarce literature is observed regarding the tissue formed in the root canal. A four-year radiographic follow-up with histologic findings in an immature mandibular premolar with dens evaginatus that underwent a regenerative endodontic procedure (REP) is presented here. After four years following REP, the tooth was extracted for orthodontic purposes thereby presenting an opportunity to report the histologic findings. Summary: The radiographic changes included a slight root lengthening and thickening and apex closure. Histologic evaluation revealed a fibrous connective tissue with an inflammatory infiltrate in the canal space. In the apical region, cementum-like irregular mineralization developed toward the center, giving the appearance of a closed apex. Root thickening, increase in length, and radiographic closure of the apex occurred due to cemental hyperplasia. Conclusion: After 4 years following REP in an immature mandibular premolar with apical periodontitis, granulation tissue had formed in the root canal, indicating repair and not regeneration.